2020
DOI: 10.1371/journal.pone.0235355
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Funneliformis mosseae enhanced with titanium dioxide nanoparticles (TiO2NPs) on Phaseolus vulgaris L. under salinity stress

Abstract: The Arbuscular mycorrhizal fungi (AMF) ( Funneliformis mosseae ), are the most widely distributed symbiont assisting plants to overcome counteractive environmental conditions. In order to improve the sustainability and the activity of AMF, the use of nanotechnology was important. The main objective of this study was to investigate the effect of titanium dioxide nanoparticles (TiO 2 NPs) on the activity of AMF in common bean roots as well as its activity under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 61 publications
5
28
0
Order By: Relevance
“…The ion source temperature was set at 200 °C. Compounds were identified by comparison of their retention times and mass spectra with those of WILEY 09 and the National Institute of Standards and Technology 2011 mass spectral library (NIST 11) [ 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ion source temperature was set at 200 °C. Compounds were identified by comparison of their retention times and mass spectra with those of WILEY 09 and the National Institute of Standards and Technology 2011 mass spectral library (NIST 11) [ 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…168 However, recent studies showed beneficial effects: Ag NPs (5 nm mean size) stimulated the formation of mycorrhizae in seedlings of pedunculate oak (Quercus robur L.), 169 and biologically synthesized TiO 2 NPs (68 nm mean size) enhanced root colonization of common bean (Phaseolus vulgaris L.) with the arbuscular mycorrhizal fungi (Funneliformis mosseae) and improved salinity tolerance compared to inoculation with arbuscular mycorrhizal fungi alone. 170 These seemingly contradictory results expose the complexity of the relations involved and highlight the necessity to consider every experimental parameterin particular, precise optimization of doses and modes of application. 169,170…”
Section: Effects Of Nanoparticles In Soil and Soil Microbiotamentioning
confidence: 99%
“…170 These seemingly contradictory results expose the complexity of the relations involved and highlight the necessity to consider every experimental parameterin particular, precise optimization of doses and modes of application. 169,170…”
Section: Effects Of Nanoparticles In Soil and Soil Microbiotamentioning
confidence: 99%
“…In this framework, nanotechnology offers the ability to control matter at the nanoscale to have unique physical or chemical merits due to their small diameter, morphology or large surface area ( El-Gazzar and Enan, 2020 , El-Gazzar and Ismail, 2020 ). Nanotechnology is also used to prevent the formation of pollutants to treat and remediate contaminated water or contaminants by applying the material technology, industrial processes and others ( El-Gazzar et al, 2020 ). Biosyntheses applied by fungi might appear attractive for nanoparticles in wider rate because they have a potentiality with standing during different conditions of bioprocesses due to their filamentous nature ( Kar et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%